2020
DOI: 10.1111/cas.14267
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous CXCL9 affects prognosis by regulating tumor‐infiltrating natural killer cells in intrahepatic cholangiocarcinoma

Abstract: CXCL9, an IFN-γ inducible chemokine, has been reported to play versatile roles in tumor-host interrelationships. However, little is known about its role in intrahepatic cholangiocarcinoma (iCCA). Here, we aimed to elucidate the prognostic and biological implications of CXCL9 in iCCA. Endogenous CXCL9 expression and the number of tumor-infiltrating lymphocytes were immunohistochemically assessed in resection specimens. These data were validated in mice treated by silencing CXCL9 with short hairpin RNA. In addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 41 publications
(57 reference statements)
0
54
0
Order By: Relevance
“…CXCL9 has been identified as a tumor suppressor, because in 70 iCCA resection specimens high levels of CXCL9 were associated to a favorable postoperative survival. High CXCL9 also correlated with remarkable abundance of tumor-infiltrating NK cells [ 87 ]. The protective role of CXCL9 was confirmed in a mouse model of iCCA, in which CXCL9 knockdown led to greater tumor masses, affecting NK cell recruitment into tumor areas.…”
Section: Cxcl9/cxcr3mentioning
confidence: 99%
See 1 more Smart Citation
“…CXCL9 has been identified as a tumor suppressor, because in 70 iCCA resection specimens high levels of CXCL9 were associated to a favorable postoperative survival. High CXCL9 also correlated with remarkable abundance of tumor-infiltrating NK cells [ 87 ]. The protective role of CXCL9 was confirmed in a mouse model of iCCA, in which CXCL9 knockdown led to greater tumor masses, affecting NK cell recruitment into tumor areas.…”
Section: Cxcl9/cxcr3mentioning
confidence: 99%
“…Moreover, exposure of CCA cells to CXCL9 did not modify either invasion or proliferation rate. These data suggest that boosting the CXCL9 system could represent a promising therapeutic approach, being involved in immunopotentiation [ 87 ].…”
Section: Cxcl9/cxcr3mentioning
confidence: 99%
“…On the contrary, NK cells are cytotoxic innate cells with the capacity to destroy tumor cells in an antigen-nonspecific manner [77], but less is known about the role of NK cells in CCA. However, in vitro and in vivo studies demonstrated that the endogenous iCCA CXCL9 correlates with the higher infiltrations of NK cells in the tumor zones [78] and that the biliary epithelium could present antigens to and activate NK T cells [79].…”
Section: Innate Immune Cellsmentioning
confidence: 99%
“…The use of in vitro cytokine-activated NK cells in combination with cetuximab, the mAb against EGFR, has shown benefits in a higher antibody-dependent cellular cytotoxicity response against human iCCA cell lines such as HuCCT-1 and OZ[ 183 ]. Moreover, the multiple infusions of ex vivo -expanded human NK cells into iCCA xenograft mice (HuCCT-1 tumor-bearing nude mice) resulted in NK cell-mediated cytolytic response with inhibition of tumor growth[ 184 ].…”
Section: Iccamentioning
confidence: 99%